BMI Does Not Affect Complications or Patient Reported Outcomes After Lumbar Decompression Surgery. Issue 10 (December 2020) - Divi, Srikanth N.; Goyal, Dhruv K.C.; Stull, Justin D.; Kothari, Parth; Padua, Fortunato G.; Patel, Parthik D.; Bowles, Daniel R.; Reyes, Ariana A.; Galetta, Matthew S.; Kaye, Ian D.; Kurd, Mark F.; Woods, Barrett I.; et al.
Abstract : Study Design: This is a retrospective comparative review. Objective: The objective of this study was to identify the influence of body mass index (BMI) on postsurgical complications and patient reported outcomes measures (PROMs) following lumbar decompression surgery. Summary of Background Data: Current literature does not accurately identify the impact of BMI on postsurgical complications or outcomes. Materials and Methods: Records from a single-center, academic hospital were used to identify patients undergoing 1 to 3-level lumbar decompression surgery. Patients under 18 years of age, those undergoing surgery for infection, trauma, tumor, or revision, and those with <1-year follow-up were excluded. Patients were split into groups based on preoperative BMI: class I: BMI <25.0 kg/m 2 ; class II: BMI 25.0–29.9 kg/m 2 ; class III: BMI 30.0–34.9 kg/m 2 ; and class IV: BMI >35.0 kg/m 2 . Absolute PROM scores, the recovery ratio and the percent of patients achieving minimum clinically important difference between groups were compared and a multiple linear regression analysis was performed. Results: A total of 195 patients were included with 34 (17.4%) patients in group I, 80 (41.0%) in group II, 49 (25.1%) in group III, and 32 (16.5%) in group IV. Average age was 60.0 (58.0, 62.0) years and average follow-up was 13.0 (12.6, 13.4) months. All patients improved significantly within each group, except for class III and class IV patients, who did not demonstrate significant improvements in terms of Mental Component Score (MCS-12) scores ( P =0.546 and 0.702, respectively). There were no significant differences between BMI groups for baseline or postoperative PROM values, recovery ratio, or the percent of patients reaching minimum clinically important difference. Multiple linear regression analysis revealed that BMI was not a significant predictor for change in outcomes for any measure. The 30-day readmission rate was 6.2% and overall revision rate at final follow-up was 5.1%, with no significant differences between groups. Conclusion: This study's results suggest that BMI may not significantly affect complications or patient outcomes at 1-year in those undergoing lumbar decompression surgery. Level of Evidence: Level III.